The influence of agile leadership, motivation of entrepreneurial, and organizational culture on the Performance of Creative Economy MSMEs on Lombok Island - Nururly, Santi; Burhanudin, Burhanudin; Suprayetno, Djoko; Sriningsih, Siti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The Covid-19 pandemic has encouraged efforts to recover the national economy through the MSME sector, which is important for the economy. This sector, while vital, has also been negatively affected by the pandemic. In a difficult economic situation, special attention to MSMEs is important because internal and external factors affect business performance. In addition, adaptability (agility) and entrepreneurial motivation also have a significant role in facing this challenge. The purpose of this study is to determine the relationship between Agile leadership, motivation of entrepreneurial, and organizational culture on the performance of creative economy MSMEs on Lombok Island. The study used quantitative methods by taking respondents from entrepreneurs or owners of creative economy MSMEs, especially food and baverage (culinary). The output produced is the National Journal with ISSN and teaching materials that enrich entrepreneurship learning materials and human resources.